THE RELEVANCE OF THE UNIVERSITY CURRICULUM IN OVERCOMING SKILL MISMATCH IN THE ISLAMIC BANKING SECTOR - Ulfa Hidayati; Muzdalifah Muhammadun; Muhammad Madir; Nur Alya; Ashara Sakina (MARGIN: Journal of Islamic Banking, 2026)
Islamic banking in Indonesia continues to grow rapidly in line with increasing public awareness of the importance of a financial system that complies with sharia principles. (Irhamni et al., 2023) This is supported by data from the Financial Services Authority (OJK), which notes that Islamic banking assets have shown significant growth in Indonesia in recent years. According to the OJK report, total assets of Islamic commercial banks increased from IDR 254,184 billion in 2016 to IDR 586,055 billion in 2024, indicating an average annual growth of around 10% or more, as seen in Graph 1. However, this industry growth presents new challenges, particularly in terms of providing competent human resources (HR) relevant to industry needs. The rapid growth of the Islamic banking sector in Indonesia not only reflects growing public awareness of Islamic financial principles but also demonstrates a significant opportunity for higher education institutions to play an active role in developing competent human resources aligned with industry needs. However, amidst this rapid growth, a serious challenge arises in the form of a mismatch between the competencies of university graduates and the actual needs of the Islamic banking sector, known as a skills mismatch. According to the 2023 Islamic Finance Development Indicator (IFDI) report, Indonesia ranks first in global Islamic financial development, with significant contributions from the Islamic banking sector. However, the main challenge facing this industry is the lack of professional workers with specific competencies in modern Islamic finance and banking (IFDI, 2023). A similar sentiment was echoed by the Financial Services Authority (OJK, 2024), which highlighted that the growth of assets and expansion of Islamic financial institutions is not matched by the availability of human resources with technical expertise, regulatory understanding, and strong Islamic ethical values. This skills mismatch phenomenon demonstrates the gap between education and industry (World Bank, 2022). While many universities have opened Islamic economics or banking study programs, the curriculum often remains theoretical and does not fully reflect the needs of the dynamic Islamic finance industry. Several previous studies, such as those conducted by (Putri, 2019) shows that around 60% of Islamic economics graduates do not yet have the competencies that meet the work standards in Islamic financial institutions, especially in the aspects of financial technology (fintech), digital literacy, Islamic risk management, and Islamic banking product innovation. Skills mismatch not only harms graduates but also the industry, as it increases training and development costs. This research is crucial to identify the extent to which current university curricula are relevant to the needs of the Islamic banking sector and to provide concrete recommendations to reduce this gap. By improving curriculum relevance, universities can enhance graduate competitiveness and support the sustainable growth of the Islamic banking sector. Skills mismatch in Indonesia is a significant issue in the labor market, characterized by a mismatch between the skills of the workforce and industry needs. Data shows that in 2015, vertical mismatch reached 53.33%, while horizontal mismatch reached 60.52%. (Hasibuan, 2019) Another 2019 study indicated that 27.9% of the workforce is overeducated, and 68.4% experience a field of study mismatch. Therefore, addressing the skills mismatch requires collaboration between the government, educational institutions, and industry to align curricula with job market needs and provide relevant training for the workforce. (Dianita Pramesti et al., n.d.) A study in the An Najah Journal highlights a significant gap between the competencies possessed by university graduates and current job market needs. This is evidenced by the high educated unemployment rate in Indonesia, which reached 2.09% in February 2023. (SINTA, 2023) The study examined the phenomena of overeducation and horizontal mismatch among employees in the Indonesian garment industry. The results showed that 67.61% of workers experienced educational mismatch, with 68% of them experiencing overeducation. In this context, research on the relevance of higher education curricula in addressing the skills mismatch in the Islamic banking sector is crucial and urgent. This research seeks to determine the extent to which higher education curricula prepare graduates to meet the demands of the contemporary Islamic finance industry, as well as how synergies between educational institutions, regulators, and industry can be strengthened. In addition, this research has strategic relevance to national policies, particularly the Independent Learning – Independent Campus (MBKM) program, which emphasizes the importance of collaboration between higher education and the workplace to create adaptive, creative, and competitive graduates. (Kemendikbud, 2024). Through this research, it is hoped that a collaborative curriculum model based on industry needs (industry-driven curriculum) can be found that is able to bridge the competency gap, strengthen the technical and non-technical skills of graduates, and support the realization of an inclusive and sustainable national sharia economic ecosystem. Thus, this research not only provides academic contributions in the development of curriculum relevance theory, but also provides practical benefits for the world of higher education, the Islamic banking industry, and policy makers in developing superior human resources that are globally competitive and based on Islamic values.